Effect of invasive acupuncture on awakening quality after general anesthesia: systematic review and meta-analysis - Bu, Fan-dong; Si, Shang-kun; Zhang, Dong-bin; Chi, Yong-liang (Frontiers in Medicine, 2025)
BackgroundThe process of waking up from general anesthesia is still not well understood, and recovery issues such as delayed awakening, agitation, postoperative cognitive dysfunction, continue to be a challenge for anesthesiologists. Currently, the treatment of these complications is mainly achieved through the antagonistic action of specific drugs, but sometimes the antagonistic drugs are not as effective as they should be and can add to the financial burden of the patient. Acupuncture, a common treatment in Traditional Chinese Medicine, is widely used around surgery. However, there is no enough evidence to show it improves recovery after anesthesia. To explore this, we reviewed relevant randomized trials and conducted a meta-analysis.ObjectiveThis systematic review was conducted to explore the effect of perioperative application of invasive acupuncture on the quality of postoperative awakening after general anesthesia.MethodsBy searching PubMed, Embase, Cochrane Clinical Trials Center, China Knowledge Network (CNKI), China Biomedical Database (CBM), Wanfang Medical Database, Weipu Database, to include randomized controlled trials of invasive acupuncture applied perioperatively. Search is limited from the build-up of the database to March 2022. The statistical analysis was conducted using RevMan 5.3. Quality assessment of the included research literature using Cochrane-recommended risk of bias assessment tool.Results18 randomized controlled trials were included with 1,127 patients. 565 patients in invasive acupuncture intervention group, 562 patients in control group. Results showed that invasive acupuncture group had a shorter eye opening time than control group (MD = −6.42, 95% CI [−8.17, −4.66], p < 0.001), shorter extubation times (MD = -5.84, 95% CI [−8.12, −3.56], p < 0.001), lower MAP at extubation (MD = −18.54, 95% CI [−22.69, −14.39], p < 0.001), lower HR at extubation (MD = −14.85, 95% CI [−23.90, −5.81], p < 0.001). No statistical difference in the occurrence of POCD (OR = 0.56, 95% CI [0.28, 1.11], p = 0.10) and postoperative agitation (OR = 0.42, 95% CI [0.11, 1.65], p = 0.21).Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, CRD42023410260.